Fenestrated stent grafts for the treatment of complex aortic aneurysm disease: A mature treatment paradigm. (June 2016) - Georgiadis, George S; van Herwaarden, Joost A; Antoniou, George A; Giannoukas, Athanasios D; Lazarides, Miltos K; Moll, Frans L
The introduction of fenestrated stent grafts (SGs) to treat abdominal aortic aneurysms (AAAs) with short proximal necks began in 1999. Nowadays, the whole visceral aorta can be treated totally by endovascular means. The established use of fenestrated devices to treat complex AAAs as a first-line management option has been previously reported. An up-to-date evaluation of the literature was performed including all types of publications regarding the use of fenestrated technology to repair complex AAAs. Fenestrated repair is now an established alternative to hybrid/chimney/snorkel repairs. However, specific criteria and prerequisites are required for the use and improvement of this method. Multiple device morphologies have been used incorporating the visceral arteries in various combinations. This modular strategy connects different devices (bridging covered stents and bifurcated SGs) with the aortic main body, thus excluding the aneurysm from the circulation. Precise deployment of the fenestrated SG is mandatory for successful visceral vessel revascularization. Accurate SG sizing and customization, a high level of technical skill, and facilities with modern imaging techniques including 3D road mapping and dedicated hybrid rooms are required. Most experience has been with the custom-made Zenith Cook platform, although off-the-shelf devices have been recently implanted. More complex repairs have been performed over the last few years, but device complexity has also increased. Perioperative, mid-term, and a few recently reported long-term results are encouraging. Secondary interventions remain the main problem, similar to that observed after traditional endovascular abdominal aortic aneurysm repair (EVAR).